Plant‐Derived Stilbenoids as DNA‐Binding Agents: From Monomers to Dimers. Issue 34 (14th May 2021) - Platella, Chiara; Mazzini, Stefania; Napolitano, Ettore; Mattio, Luce M.; Beretta, Giovanni Luca; Zaffaroni, Nadia; Pinto, Andrea; Montesarchio, Daniela; Dallavalle, Sabrina
Abstract: Stilbenoids are natural compounds endowed with several biological activities, including cardioprotection and cancer prevention. Among them, (±)‐ trans ‐δ‐viniferin, deriving from trans ‐resveratrol dimerization, was investigated in its ability to target DNA duplex and G‐quadruplex structures by exploiting NMR spectroscopy, circular dichroism, fluorescence spectroscopy and molecular docking. (±)‐ trans ‐δ‐Viniferin proved to bind both the minor and major grooves of duplexes, whereas it bound the 3'‐ and 5'‐ends of a G‐quadruplex by stacking on the outer quartets, accompanied by rearrangement of flanking residues. Specifically, (±)‐ trans ‐δ‐viniferin demonstrated higher affinity for the investigated DNA targets than its monomeric counterpart. Additionally, the methoxylated derivatives of (±)‐ trans ‐δ‐viniferin and trans ‐resveratrol, i. e. (±)‐pterostilbene‐ trans ‐dihydrodimer and trans ‐pterostilbene, respectively, were evaluated, revealing similar binding modes, affinities and stoichiometries with the DNA targets as their parent analogues. All tested compounds were cytotoxic at μM concentration on several cancer cell lines, showing DNA damaging activity consistent with their ability to tightly interact with duplex and G‐quadruplex structures. Abstract : The stilbenoid (±)‐ trans ‐δ‐viniferin, deriving from trans ‐resveratrol dimerization, binds to minor and major grooves of B‐DNA, and to 3'‐ and 5'‐ends of G‐quadruplex DNA by stacking on the outer quartets accompanied by rearrangement of flanking residues. Consistent with the ability to tightly interact with different DNA secondary structures, (±)‐ trans ‐δ‐viniferin shows DNA damaging activity.